Funções da comercialização dos produtos agrícolas - Leitão e Silva, Josué (Revista Ceres, 2025)
This is a brief marketing study of farm products with emphasis on selection, standardization and inspection. Each element was studied by the usual techniques employed in the author’s country, in as effort to determine their effect upon the organization of production.